ОРГАНИЗАЦИЯ САМОСТОЯТЕЛЬНОЙ РАБОТЫ СТУДЕНТОВ ПРИ ИЗУЧЕНИИ ФИЗИКИ - Касымов, С.М. (SCIENCE and SOCIETY, 2024)
This article talks about the importance and formation of independent work of students when studying physics. Independent work of students includes the necessary elements of the process of studying physics. This method of teaching allows students not only to deepen their knowledge of physics, but also to engage in scientific research, critical thinking and independent work.
Keywords: independent work of student; physics; education; methodology; scientific research; educational process